Urban Mobility in African Cities : Developing National Urban Mobility Policy and Delivering at the City Level - Summary Report - World Bank (Washington, DC, 2022)
African cities are growing at an extraordinary rate. Unfortunately, many cities are growing so fast that national, provincial, and city governments cannot manage how they develop or assure the provision of the services people need. This has many negative consequences for national and city economies and the people who live in these areas. Urban mobility is one of the key challenges for African cities. In many cities, the transport system has failed to keep up with urban growth. There is inadequate provision of dependable, affordable, and safe transport services to meet the travel needs of the people. Private vehicle ownership and use is increasing, congesting the roads. The informal sector provides much of the general transport service, using very large numbers of small vehicles. At the same time, the travel system impacts the city through congestion, increased costs, pollution, accidents, noise, intrusion, and long delays for both users and non-users. Cities cannot resolve these things alone. National Governments need to lead by guiding the development of cities, developing urban mobility policies, improving the implementation frameworks, and mobilizing finance. Critical to this strategy is ensuring city level capabilities are built to develop and implement locally appropriate strategies. The Africa Transport Policy Program (SSATP) aims to provide African decision-makers with the tools necessary to support the implementation of such policies and measures. Within this work, SSATP has developed guidance and prepared specific recommendations for urban mobility policy for 12 Sub-Saharan African countries. This note also provides a concise synthesis of the key issues and guidance, which can then be read in detail in the technical reports.